PENYELESAIAN PEMBIAYAAN BERMASALAH DALAM PRODUK PEMBIAYAAN MURABAHAH (STUDI PADA PT. BPRS MUAMALAT HARKAT SUKARAJA) - Elwardah, Khairiah (Institut Agama Islam Bengkulu, 2019)
The purpose of this study was to determine the causes of problematic financing that occurred in murabahah financing products and explain the procedure for solving problematic financing in murabahah financing products at PT. BPRS Muamalat Harkat Sukaraja with DSN-MUI Fatwa No: 48 / DSN-MUI / II / 2005 concerning the Rescheduling of Murabahah and Fatwa Bills for the National Sharia Board No: 25 / DSN-MUI / III / 2002 About Rahn. To disclose the matter, researchers use a qualitative approach. Data was obtained through interviews with employees of BPRS Muamalat Harkat in the Finance section and customer service of BPRS Muamalat Harkat Sukaraja. Data is also obtained from brochures of BPRS Muamalat Harkat Sukaraja. The data analysis technique used was the interactive model of Miles and Huberman. The results of the study conclude that the problematic financing that occurred in murabahah financing products at BPRS Muamalat Harkat Sukaraja was caused by a decrease in the level of debitor income. The settlement of problematic financing cases conducted by BPRS Muamalat Harkat Sukaraja is in accordance with the Fatwa of the National Sharia Board No: 48 / DSN-MUI / II / 2005, and the Fatwa of the National Sharia Council No: 25 / DSN-MUI / III / 2002.